PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA PPT INTERAKTIF TERHADAP HASIL BELAJAR IPS MATERI EKSPOR DAN IMPOR SISWA KELAS VI SDN TELANG 2 - Soviati; Sestri Aulia Rahman; Ika Dian Rahmawati (STKIP Subang, 2026)
This study aims to find out the effect of the Contextual Teaching and Learning (CTL) model assisted by interactive PowerPoint (PPT) media on the social studies learning outcomes of 6th-grade students at SDN Telang 2 on the topic of exports and imports. This research uses a quantitative approach with a pre-experimental method and a One Group Pretest-Posttest Design. The research sample consisted of 20 students selected using a total sampling technique. Data collection was done through learning outcome tests in the form of pretests and posttests. The data were analyzed using normality tests, N-Gain tests, and Paired Sample t-Tests. The results showed that the average pretest score of students was 58.25 and increased to 84.50 in the posttest. The N-Gain calculation resulted in a score of 0.63, which falls into the medium category. In addition, the Paired Sample t-Test showed a Sig. (2-tailed) value of 0.000 < 0.05, which means H₀ was rejected and Hₐ accepted. The results show that there is a significant effect of using the CTL model assisted by interactive PPT on the social studies learning outcomes for sixth-grade students at SDN Telang 2 on the topic of exports and imports. Therefore, the CTL model assisted by interactive PPT can be used as an effective alternative learning method to improve students' learning outcomes in social studies. Keywords: Contextual Teaching and Learning (CTL), Interactive PowerPoint, Learning Outcomes, Social Studies, Export and Import.